Filtration Rate of the Solitary, Pleated Tunicate Styela plicata on the Brown Tide-Forming Pelagophytes Aureoumbra lagunensis and Aureococcus anophagefferens - Klarmann, Phyllis A.; Scarpa, John; Hartmann, James X. (Frontiers in Marine Science, 2022)
Recurring brown tide algal blooms of the pelagophyte Aureoumbra lagunensis in the northern Indian River, Mosquito, and Banana River lagoons on the Atlantic coast of central Florida, USA, have resulted in marked ecological impacts. Recent studies have investigated whether suspension feeding invertebrates could contribute to top-down control of these and other bloom-forming phytoplankton. While most studies focused on the effects A. lagunensis has on on bivalve filter feeding in the Indian River Lagoon, this study focused on feeding by the solitary pleated tunicate Styela plicata. Hourly filtration rates (FR) of individual S. plicata were measured after exposure to 5.0 x 105 cells mL–1 of either A. lagunensis or another pelagophyte Aureococcus anophagefferens. The latter species has not been observed in Florida estuaries but can also inhibit feeding. Tisochrysis lutea, an alga commonly used as feed in aquaculture was used as a control. Differences in hourly FR of either brown tide species compared to the control alga were statistically significant (p < 0.0001). Mean hourly FR of tunicates exposed to Aureoumbra lagunensis ranged from -282 mL hr−1 to 542 mL hr−1, whereas tunicates exposed to the control species Tisochrysis lutea had FR from 285 mL hr−1 to 2648 mL hr−1. Mean hourly FR of tunicates exposed to Aureococcus anophagefferens ranged from 343 mL hr−1 to 593 mL hr−1 compared to tunicates exposed to T. lutea which ranged from 600 mL hr−1 to 2482 mL hr−1. Further, to test whether cell density and a longer exposure time affected FR, individual S. plicata were initially exposed to cell densities of 103, 104, or 105 cells mL–1 of either A. lagunensis or T. lutea (control) for 24 hours. Subsequent measurement of hourly FR and showed cell density removal was not significantly different (p = 0.28 and 0.77, respectively). These results add to the body of literature on how organisms in the Indian River Lagoon filter-feeder community respond to brown tide exposure. The pleated tunicate may be an additional species contributing to top-down control of these bloom-forming microalgae.